Professional rugby league positional match-play analysis through the use of global positioning system - Austin, D. J.; Kelly, S. J. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to quantify the movement demands of all 9 individual playing positions in professional rugby league. The movement demands of 135 professional rugby league players were recorded during 28 National Rugby League games in 2011, using a nondifferential 5 Hz global positioning system. The mean total distances covered in a game for fullback, wing, center, five-eight, halfback, hooker, lock, back row, and prop players were 7,760, 7,457, 7,301, 8,402, 8,500, 6,988, 5,481, 6,936, and 4,597 m, respectively. The average occurrence of high-intensity runs per match was 42, 35, 34, 86, 120, 74, 52, 26, and 18 for fullback, wing, center, five-eight, halfback, hooker, lock, back row, and prop players, respectively. The average distance traveled greater than 18 km/h for fullback were 17 ± 2 m, wing 18 ± 2 m, center 18 ± 3 m, five-eight 16 ± 3 m, and halfback 17 ± 4 m. The average distance and range traveled greater than 18 km/h for hooker were 14 ± 3 m, lock 16 ± 2 m, back row 18 ± 3 m, and prop 16 ± 2 m. The use of global positioning systems has demonstrated plausibility to eliminate the use of grouping of positions in rugby league and for coaches to make specific training protocols for each position. Given the differences in movement demands of all 9 positions in rugby league, some positions would lack specificity to their positional requirements if using collective grouping for planning of training regimens.